A micro review on the role of recently emerged Artificial Intelligence (AI) tools and algorithms in microbiome-gut-brain-axis associated disease therapy via psychobiotics - Lim, Leonard Whye Kit (Precision Medication, 2025)
The microbiome-gut-brain axis involves the bidirectional connection between the gastrointestinal tract, gut microbiome, and central nervous system, and it is pivotal for mental well-being. Imbalances in the gut microbiome (dysbiosis) can disrupt neurotransmitter synthesis, leading to neurodegenerative diseases. Recent researches highlight psychobiotics as effective treatments for mental health conditions like depression. With advancements in artificial intelligence (AI) and large datasets, psychobiotic research has accelerated. AI tools are increasingly used for the prediction, identification, and diagnosis of gut microbiome compositions, enabling faster and more accurate discovery of therapeutic candidates. This review explores the role of AI in enhancing microbiome-gut-brain-axis-related disease therapies through psychobiotics and discusses future directions for this rapidly evolving research field.